2017
DOI: 10.1002/gps.4761
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depressive and anxiety symptoms in older adults: a 6‐year prospective cohort study

Abstract: Our results indicate distinct and sex-specific risk factors linked to depressive and anxiety trajectories, which may help inform risk stratification and management of these symptoms in older adults at risk for Alzheimer's disease. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 69 publications
(84 reference statements)
8
27
1
Order By: Relevance
“…Cognitive dysfunction, particularly executive dysfunction, is common in geriatric depression and increases the risk for poor response to antidepressants . However, findings on the association between cognitive impairment and the clinical course of depression have been divergent in both clinical‐ and population‐based samples, with some studies reporting significant associations and some reporting null findings . Separate processes may be involved in specific domains of cognition and response to depression treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive dysfunction, particularly executive dysfunction, is common in geriatric depression and increases the risk for poor response to antidepressants . However, findings on the association between cognitive impairment and the clinical course of depression have been divergent in both clinical‐ and population‐based samples, with some studies reporting significant associations and some reporting null findings . Separate processes may be involved in specific domains of cognition and response to depression treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Trajectory groups with greater symptom burden were associated with female sex, low income and education, limited social support, functional impairment, physical illnesses, and initial symptom severity . Difference in the shape of depression trajectories by age groups has also been reported, while findings regarding the impact of cognition have been mixed …”
Section: Introductionmentioning
confidence: 99%
“…Person-centred methods have highlighted the presence of varying, heterogeneous trajectories of depressive symptoms (Holmes et al, 2017;Hsu, 2012;Kuchibhatla et al, 2012). Recently, a systematic review has provided consistent evidence on depressive symptom trajectories, underlying the overall course, across the lifespan (Musliner et al, 2016).…”
Section: Long-term Trajectories Of Depressive Symptoms In Old Age: Rementioning
confidence: 99%
“…In these models, underlying subgroups within a population are identified and a growth curve for each subgroup is estimated . Several studies have examined trajectories of depressive symptoms and found symptom development to be highly heterogeneous . However, these studies were either conducted among the general population or among patients suffering from unipolar depressive disorder .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined trajectories of depressive symptoms and found symptom development to be highly heterogeneous . However, these studies were either conducted among the general population or among patients suffering from unipolar depressive disorder . Only few clinical studies have performed trajectory analyses to explore symptom development among patients with bipolar disorder, and none of these have investigated how depressive symptoms improve over time .…”
Section: Introductionmentioning
confidence: 99%